Demographic Transition and the Development of Indonesia - Priyono, P (Forum Geografi, 1990)
The Indonesian population is still growing rapidly and it is induced by fertility and mortacity aspect. In the period of 1961-1971, the overage rate of population growth was 2.1 percent and it became 2.34 percent in the next decade. After that a decrease occured in the period of 1980-1985 (2.1 percent). The decrease in the growth rate lasted to the year of 1990 (1.9 percent). The increase in population in the period of 1971 â 1980 did not mean the failures of the development programmes, like education, health, family planning, the women rate etc but it was due to the decrease in mortality rate was faster than the decrease in fertility rate in the demographic transition era. The development intervention, as stated set forth, has induced the decrease in fertility and mortality in this country, though different intensity. The special province of Yogyakarta and Bali their transition wheieas Nusa Tenggara Barat province is still far from the end of transition. The development impact will life expectancy, death rate, infant mortality rate etc.